Competitive ability of common bean cultivars in the presence of Urochloa plantaginea - Otilo Daniel Henz Neto; Janaíne Oliveira Toso; Leandro Galon; Caroline Müller; Cesar Tiago Forte; Leonardo Brunetto; João Paulo Giacomini; Gismael Francisco Perin (Revista de Ciencias Agrícolas, 2023)
Weeds are the main constraints to high bean productivity. Here, we aimed to investigate the competitive ability of black type bean cultivars BRS Campeiro and SCS Predileto in coexistence with alexandergrass, Urochloa plataginea. The experimental design employed a replacement series arrangement, and the experiments were conducted in a greenhouse using a randomized block design with four replicates. Once the appropriate plant density was determined, the experiments proceeded with the following ratios of bean to U. plataginea plants per pot: 20:00, 15:5, 10:10, 5:15, and 0:20. Fifty-five days after the emergence of the plants, physiological and morphological traits were analyzed. Diagrams were made to analyze the relative productivity (RP), total relative productivity (TRP), and the competitiveness indices. Based on RP and TRP, a similar competitive mechanism for environmental resources was observed for both bean cultivars in the presence of U. plataginea. Variables such as leaf area, dry matter, stem diameter, and plant height of the bean cultivars were negatively affected by U. plataginea, indicating a superior competitive ability for environmental resources. However, considering only the 10:10 plants per plot ratio, beans showed higher relative growth than U. plataginea, represented by relative competition indices, relative clustering coefficients, and aggressiveness. Intraspecific competition was found to be more harmful than interspecific competition for both crop and weed species.